Taurine and Epidermal Growth Factor Belong to the Signature of First-Episode Psychosis - Koido, Kati; Innos, Jürgen; Haring, Liina; Zilmer, Mihkel; Ottas, Aigar; Vasar, Eero (Frontiers in Neuroscience, 2016)
This study evaluated the levels of two amino acid derivatives taurine and spermine in first-episode psychosis (FEP) patients and their response to antipsychotic treatment. The levels of taurine and spermine were significantly up-regulated in antipsychotic-naïve FEP patients compared to control subjects (CS). Treatment of FEP patients with antipsychotic drugs significantly reduced the positive symptoms of schizophrenia. This positive effect was accompanied by a significant reduction of taurine and spermine to the levels measured in CS. General linear model was used to establish associations of taurine and spermine with the levels of cytokines and growth factors, measured in our previous experiments using the same study sample. There was a strong association between taurine and epidermal growth factor (EGF). Both biomarkers significantly correlated with the disease symptoms as well as with the effectiveness of antipsychotic treatment. Accordingly one can conclude that taurine and EGF belong to the signature of FEP. Most probably they reflect altered oxidative stress and corrupted function of N-methyl-D-aspartate (NMDA) receptors in FEP.